Compiling a Corpus-based Dictionary Grammar: An Example for Northern Sotho - de Schryver, Gilles-Maurice; Taljard, Elsabé (Lexikos, 2007)
Abstract: In this article it is shown how a corpus-based dictionary grammar may be compiled — that is, a mini-grammar fully based on corpus data and specifically written for use in and inte-grated with a dictionary. Such an effort is, to the best of our knowledge, a world's first. We exem-plify our approach for a Northern Sotho mini-grammar, to be included into a Northern Sotho–Eng-lish dictionary.Keywords: LEXICOGRAPHY, DICTIONARY, CORPUS, FREQUENCY, MIDDLE MATTER, DICTIONARY GRAMMAR, NORTHERN SOTHO (SESOTHO SA LEBOA)Samenvatting: Een corpusgebaseerde woordenboekgrammatica samenstel-len: een voorbeeld voor Noord-Sotho. In dit artikel wordt aangetoond hoe een corpus-gebaseerde woordenboekgrammatica kan samengesteld worden — dit is, een minigrammatica die al z'n gegevens rechtstreeks uit een corpus haalt en die speciaal geschreven werd om in een woor-denboek gebruikt te worden, en er ook volledig mee geÃ¯ntegreerd is. Zo'n poging is, voor zover ons bekend, een wereldprimeur. We illustreren onze aanpak voor een minigrammatica van het Noord-Sotho, bedoeld om gebruikt te worden in een Noord-Sotho–Engels woordenboek.Sleutelwoorden: LEXICOGRAFIE, WOORDENBOEK, CORPUS, FREQUENTIE, MID-DENWERK, WOORDENBOEKGRAMMATICA, NOORD-SOTHO